Electrochemical Properties and Reactions of Organoboronic Acid Esters Containing Unsaturated Bonds at Their α-Position. Issue 2 (1st January 2017) - Ohtsuka, Kazuhiro; Inagi, Shinsuke; Fuchigami, Toshio
Abstract : Electrochemical analyses of 2-(cynnamyl)boronic acid pinacol ester and (3-phenyl-2-propynyl)boronic acid pinacol ester, and their trimethylsilyl analogues as well as their parent compounds were comparatively studied by cyclic voltammetry measurements. We found remarkable negative shifts of the oxidation potentials of the organoboronic acid pinacol esters in the presence of fluoride ions compared to those in the absence of fluoride ions. The negative shift observed was more pronounced than that of the corresponding trimethylsilyl compounds. Such marked negative shift seems to be derived from the formation of negatively charged boron-ate complex with fluoride ions as well as β-effect of organoborate. Anodic acetoxylation of organoboronic acid pinacol esters was achieved in NaOAc/AcOH, while their alkoxylation was successfully carried out in the presence of fluoride ions.